Prospek Perkembangan Modal Koperasi Baitul Maal Wat Tamwil Seruyan Sejahtera - Rinto Alexandro, Tonich Uda (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2020)
Baitul Maal Cooperative Wat Tamwil Seruyan Sejahtera which addresses at Jalan Patimura, Kuala Pembuang 1, Seruyan Regency. This cooperative was formed on November 2, 2012 with a cooperative legal entity No: 124 / BH / XVIII.14 / IDKUMKM / 11/2012 and chaired by Ir. H. Tarwidi Tamasaputra. This study uses a qualitative approach that is descriptive analysis, with data collection techniques used are observation, interviews and documentation as well as the type of data used is time series data. The data obtained will be analyzed by the growth equation and least square trand. Based on the results of the study note that the capital development Based on the analysis in table 5 can be seen in 2013 there was a growth of 15%, but a decline in 2014 amounted to 17%. Growth that greatly increased in 2015 was 40% which was affected by the increase in membership. Whereas growth in 2016 was only 16%. The average capital growth of the Cooperative Baitul Maal wat Tamwil Seruyan Sejahtera in 2012-2016 is 9.62%. While based on table 7 it can be seen that the results of capital development forecasts at the Baitul Maal wat Tamwil Seruyan Sejahtera cooperative in 2017 amounted to Rp 396,035,361.60, in 2018 amounted to IDR 422,391,710.70, in 2019 amounted to IDR 448,748.059.80, in 2020, IDR 475,104,408.90 and in 2021 IDR 501,460,758.00. This forecast of development tends to increase from year to year in the amount of IDR 26,356,349.10. This increase was affected by the business carried out, the addition of new members and by voluntary contributions from members